Fuzzy Stability Results of Finite Variable Additive Functional Equation: Direct and Fixed Point Methods - Abdulaziz M. Alanazi; G. Muhiuddin; K. Tamilvanan; Ebtehaj N. Alenze; Abdelhalim Ebaid; K. Loganathan (Mathematics, 2020)
In this current work, we introduce the finite variable additive functional equation and we derive its solution. In fact, we investigate the Hyers–Ulam stability results for the finite variable additive functional equation in fuzzy normed space by two different approaches of direct and fixed point methods.